COMPARISON RESULT OF SINGLE TRAP MOUSETRAP AND DOUBLE TRAP MOUSETRAP IN KADE JAMRUD KADE PERAK, TANJUNG PERAK PORT, SURABAYA - Okol Sri Suharyo; Heriyanto Heriyanto; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
ABSTRACTEfforts to increase the degree of public health as high as possible are carried out by creating a clean life, eliminating breeding grounds for disease causes and agents, keeping food and beverages clean and not contaminated by disease-causing and intermediate bacteria, and implementing healthy habits. Rats are nuisance animals that harm humans because they eat all types of food eaten by humans. The Rat can become agents of several pathogens that cause disease in humans because the relationship between rats and humans is often parasitic, one of which is PES. The disease can be transmitted directly by saliva urine, and feces, or through ectoparasite bites in rats (fleas, fleas, and mites). This type of research aims to see the efficiency level of single trap type mouse trap with double trap type in Kade Jamrud and Kade Perak, Tanjung Perak Port, Surabaya. This type of research is pre-experimental with a one-shot case study design, that is, in this design, the treatment or intervention has been carried out (X), then the measurement (observation) or post-test (O) is then analyzed in statistical calculations using the t-test calculation. with a significant level of 5%, to find out which type of trap is the most effective compared to other types of traps. The results of this study indicate that out of 200 traps placed in 5 different warehouses, each warehouse has 40 traps with the same composition ratio. During the study, the number of a rat trapped was 14. The double trap mouse trap received the highest number of rats, namely 10 or 71.4%, while the single trap mousetrap only received 4 or 28.6%. From the results of the study, a statistical test was carried out where the t count the source of treatment variation was 1.630 while t table was 1.860, so it can be concluded that between single trap and double trap mouse traps showed no significant difference in the number of a rat trapped.Keywords: Single Trap, Double Trap, t-test.